Successful Immunotherapy against a Transplantable Mouse Squamous Lung Carcinoma with Anti–PD-1 and Anti-CD137 Monoclonal Antibodies. Issue 4 (April 2016) - Azpilikueta, Arantza; Agorreta, Jackeline; Labiano, Sara; Pérez‐Gracia, José Luis; Sánchez‐Paulete, Alfonso R.; Aznar, Angela M.; Ajona, Daniel; Gil‐Bazo, Ignacio; Larrayoz, Marta; Teijeira, Alvaro; Rodriguez‐Ruiz, María E.; Pio, Ruben; et al.
ABSTRACT : Introduction: : Anti–programmed cell death 1 (anti–PD‐1) and anti–programmed cell death ligand 1 (PD‐L1) antagonist monoclonal antibodies (mAbs) against metastatic non–small cell lung cancer with special efficacy in patients with squamous cell lung cancer are being developed in the clinic. However, robust and reliable experimental models to test immunotherapeutic combinations in squamous lung tumors are still lacking. Methods: : We generated a transplantable squamous cell carcinoma cell line (UN‐SCC680AJ) from a lung tumor induced by chronic N ‐nitroso‐tris‐chloroethylurea mutagenesis in A/J mice. Tumor cells expressed cytokeratins, overexpressed p40, and lacked thyroid transcription factor 1, confirming the squamous lineage reported by histological analysis. More than 200 mutations found in its exome suggested potential for antigenicity. Immunocompetent mice subcutaneously implanted with this syngeneic cell line were treated with anti‐CD137 and/or anti–PD‐1 mAbs and monitored for tumor growth/progression or assessed for intratumoral leukocyte infiltration using immunohistochemical analysis and flow cytometry. Results: : In syngeneic mice, large 12‐day–established tumors derived from the transplantable cell line variant UN‐SCC680AJ were amenable to curative treatment with anti–PD‐1, anti–PD‐L1, or anti‐CD137 immunostimulatory mAbs. Single‐agent therapies lost curative efficacy when treatment was started beyond day +17, whereas a combination of anti–PD‐1 plus anti‐CD137 achieved complete rejections. Tumor cells expressed weak baseline PD‐L1 on the plasma membrane, but this could be readily induced by interferon‐γ. Combined treatment efficacy required CD8 T cells and induced a leukocyte infiltrate in which T lymphocytes co‐expressing CD137 and PD‐1 were prominent. Conclusions: : These promising results advocate the use of combined anti–PD‐1/PD‐L1 plus anti‐CD137 mAb immunotherapy for the treatment of squamous non–small cell lung cancer in the clinical setting.